PERCUTANEOUS RELEASE OF THE MEDIAL COLLATERAL LIGAMENT DURING KNEE ARTHROSCOPY - Golovakha, Maksym; Bilykh, Yevhen; Pertsov, Volodymyr (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2024)
The complete visualisation of the internal joint space is crucial for effective knee arthroscopy. However, limited access to certain areas can lead to complications, including cartilage damage. Percutaneous partial release of the medial collateral ligament has been shown to effectively widen the medial compartment of the joint. Objective. This study aimed to determine the effect of percutaneous release of the medial collateral ligament on the postoperative period and restoration of knee joint function. Methods. The patients were divided into two groups: the study group (n = 32) and the comparison group (n = 36). T he study group underwent partial resection of the medial meniscus in combination with percutaneous partial release of the medial collateral ligament, while the comparison group underwent only partial removal of the medial meniscus without widening the medial joint gap. The assessment included pain, functional recovery according to the Tegner Lisholm scale, and the possibility of developing medial instability. Results. The analysis of VAS scores showed a significant reduction in pain in both groups over time. However, there was no significant difference in pain intensity between the two groups during the study. According to the Tegner Lysholm scale, there was a statistically significant improvement in the functional status of patients 6 months after surgery compared to preoperative values in both the study group (p = 0.0034) and the control group (p = 0.0071). However, there was no statistically significant difference between the groups on t he s ame s cale ( p = 0 .871). The study g roup s howed a s light increase in valgus deviation of the tibia (no more than 5o) in 14 (43.75%) patients during the valgus stress test performed on days 7–10 postoperatively. However, after 6 weeks, none of the patients reported any subjective instability or weakness of the knee joint. Therefore, it can be concluded that the procedure was successful. Conclusion. Percutaneous release of the medial collateral ligament to widen the medial aspect during knee arthroscopy has no effect on the postoperative period or the results of partial removal of the medial meniscus.